Growth and initial yield under four planting densities and two weed managing strategies of peach palm (Bactris gasipaes K.) for palm hearts. - Bogantes-Arias, Antonio (2004)
The Study wasconducted at Los Diamantes Experiment Station, located inGuápiles, Costa Rica. Four planting densities of the spinelessvariety “Diamantes 10” (5000, 6666, 10000 and 20000plants/ha) and two weed management strategies (chemicaland physical) were compared. The parameters evaluated wereplant height, stem diameter, shoot number per plant, palmheart units harvested, industrial yield and economic income.Besides, the effect on growth of weed competition wasevaluated. Differences were observed among densities inregard to plant height and shoot number/plant at the age 9month safter planting, being higher when planted at 6666plants/ha). The higher planting densities gave the higheryields evaluated as number of stems harvested and number ofexportable boxes during the first four months harvestingperiod.